Isomorphisms on Strong Fuzzy Graphs - Trisanti, Yuliana; Saleh, Hairus (International Journal of Trends in Mathematics Education Research, 2024)
Fuzzy graph is a graph consisting of pairs of vertices and edges that have a membership degree that contains a closed interval of real numbers  on each edge and vertex. A fuzzy graph  is said to be a strong fuzzy graph if the membership degree of edge  with the minimum membership degree of vertex  and the same membership degree of vertex  for each edge  with . This paper explains the properties of fuzzy graph isomorphism including weak isomorphism, co-weak isomorphism, and isomorphism in strong fuzzy graphs.